Wind Load Effects On High-Rise Building - Tan, Yee Jin (2020)
Wind-related disasters such as windstorms, hurricanes, and sandstorms are destructive to local citizens. Numerous tragedies caused by the failure of structural members had been recorded in the past decades. Hence, structural and wind engineer plays a vital role in performing a constructive wind load analysis for tall buildings. This study aimed to evaluate the effects of wind load on highrise buildings. The objectives of this study are to evaluate the parameters used in the wind load calculation, to investigate the effects of different wind loading evaluation and to compare the building response under the ultimate condition for member forces in the shear wall and support reaction. The evaluation of wind load parameters was accomplished according to European Standard, British Standard, and Australia/New Zealand Standard. In this study, linear analysis for two building models (i.e., single building model and twin building model with a podium) were carried out using SCIA Engineer based on Eurocode (EN 1991- 1-4:2004). The output of support reactions on shear walls and columns for both building models were evaluated. Under ultimate limit state condition, the percentage difference between 14% to 57% is obtained by comparing single building model and twin building with podium Other than that, under wind load, a percentage difference of between 0% to 20% is obtained. Hence, the difference in reactions between the two building models is verified. The factors that contribute to the percentage difference are identified. Wind tunnel test and CFD simulation are recommended to improve the accuracy of results and provide firm justifications.